1996
DOI: 10.1016/0014-5793(96)00024-5
|View full text |Cite
|
Sign up to set email alerts
|

Allelic forms of the knob associated histidine‐rich protein gene of Plasmodium falciparum

Abstract: The knob associated histidine-rich protein (KAHRP) gene was cloned and sequenced from two Indian isolates of Plasmodiumfalciparum, Pf3-92 and Pf29-92. These isolates showed major sequence differences in the C-terminal repeat domain of KAHRP. However, the biologically important domains such as spectrin-actin binding region remained highly conserved. The PCR amplification of a variable C-terminal repeat domain from the clinical isolates of P. falciparum, from Rajasthan epidemic, showed the presence of multiple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Even though polymorphism in PfHRP-1 has been reported from different malaria endemic areas (Sharma and Kilejian 1987;Triglia et al 1987;Kant and Sharma 1996;Hirawake et al 1997), the present study is the first research of this kind that was conducted in Iran. The objective of this study was to investigate and analyze the extent of genetic polymorphism at the region III of KAHRP in P. falciparum isolates collected from two malaria endemic areas of Iran, including Sistan va Baluchestan and Hormozgan provinces, and to compare the frequency distribution of PfHRP-1 alleles in those areas.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Even though polymorphism in PfHRP-1 has been reported from different malaria endemic areas (Sharma and Kilejian 1987;Triglia et al 1987;Kant and Sharma 1996;Hirawake et al 1997), the present study is the first research of this kind that was conducted in Iran. The objective of this study was to investigate and analyze the extent of genetic polymorphism at the region III of KAHRP in P. falciparum isolates collected from two malaria endemic areas of Iran, including Sistan va Baluchestan and Hormozgan provinces, and to compare the frequency distribution of PfHRP-1 alleles in those areas.…”
Section: Introductionmentioning
confidence: 80%
“…The amplification conditions for primary PCR were as follows: 5 min initial denaturation at 95°C followed by 40 cycles with 1 min denaturation at 94°C, 1 min annealing at 55°C, 1 min extension at 72°C, and a final 5 min extension at 72°C. The primary PCR product was used as template in nested PCR to amplify the 402 bp region which contained the C-terminal domain of the kahrp gene with Hn-F (5′-GAAACAAAAAACACCGCTG-3′) and Hn-R (5′-GTACTGCATTAGCTCCTGTAGTTG-3′) primers (Kant and Sharma 1996). The amplification conditions for nested PCR were the same as those for primary PCR except that the number of cycles and annealing temperature were 35 cycles and 60°C, respectively.…”
Section: Pcr Amplification and Nucleotide Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of KAHRP with VARC is likely to have an electrostatic component because at the pH of the infected red cell (39), the overall charges on the histidine-rich and 5Ј repeats are positive (ϩ7 and ϩ11, respectively), whereas the overall charge on VARC is negative (Ϫ28). Allelic variation of KAHRP between different parasite isolates has revealed that the COOH-terminal region of KAHRP including the 3Ј repeats is much more highly variable than the histidine-rich and 5Ј repeats (40,41). Thus it appears as if there are greater constraints on variation of the histidine-rich and 5Ј repeats, and this may be because of their involvement in binding interactions with PfEMP1 and its role in aiding parasite survival by permitting adhesion and sequestration of infected red cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have cloned the gene of KAHRP by using oligonucleotide probe (oligos for 5 contiguous histidines) to screen a cDNA library (1). Now we have cloned this gene from various isolates to show the existence of its three allelic forms (2,3). The information on the allelic forms of KAHRP has been used in the above mentioned experiments for strain typing.…”
Section: Gene Huntingmentioning
confidence: 99%